2022
DOI: 10.1186/s12884-022-05215-8
|View full text |Cite|
|
Sign up to set email alerts
|

Do maternal albumin levels affect post-operative complications after cesarean delivery?

Abstract: Background This study explored the correlation between maternal serum albumin levels prior to elective cesarean delivery (CD) and postoperative complications. Methods This retrospective cohort study included women admitted for elective CD at term to our tertiary referral center, during the years 2016–2018. Blood samples were collected during the preoperative admission. Information collected included maternal demographics, pregnancy and postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The atlas shows that albumin and total protein concentration tests drop gradually during the first trimester, and stay low until delivery and then recover over a few weeks postpartum. This follows the temporal profile of blood volume growth, and may be attributed to uncompensated hemodilution 58 . In contrast, globulin stays relatively constant.…”
Section: Livermentioning
confidence: 80%
“…The atlas shows that albumin and total protein concentration tests drop gradually during the first trimester, and stay low until delivery and then recover over a few weeks postpartum. This follows the temporal profile of blood volume growth, and may be attributed to uncompensated hemodilution 58 . In contrast, globulin stays relatively constant.…”
Section: Livermentioning
confidence: 80%
“…Maternal SSI after cesarean delivery is a clinical problem that contributes to significant morbidity and mortality rates. We read with great interest the study by Yagur et al, who published a retrospective cohort study, the first to analyze the relationship between maternal serum albumin levels before elective cesarean delivery (CD) and postoperative complications [ 3 ]. The results suggested that high serum albumin levels among women undergoing CD might be associated with abnormal postoperative outcomes.…”
Section: Main Textmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], it was noted that due to a typesetting error the heading of the second column of Tables 1 and 2 should read “Serum albumin level < 3.3 ( n = 250).…”
mentioning
confidence: 99%